Intractable Coronavirus Disease 2019 (COVID-19) and Prolonged Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Replication in a Chimeric Antigen Receptor-Modified T-Cell Therapy Recipient: A Case Study. (28th January 2021) - Hensley, Matthew K; Bain, William G; Jacobs, Jana; Nambulli, Sham; Parikh, Urvi; Cillo, Anthony; Staines, Brittany; Heaps, Amy; Sobolewski, Michele D; Rennick, Linda J; Macatangay, Bernard J C; Klamar-Blain, Cynthia; et al.
Abstract: A chimeric antigen receptor-modified T-cell therapy recipient developed severe coronavirus disease 2019, intractable RNAemia, and viral replication lasting >2 months. Premortem endotracheal aspirate contained >2 × 10 10 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA copies/mL and infectious virus. Deep sequencing revealed multiple sequence variants consistent with intrahost virus evolution. SARS-CoV-2 humoral and cell-mediated immunity were minimal. Prolonged transmission from immunosuppressed patients is possible.